Symptomatic neonatal SARS-CoV-2 infection in a tertiary care teaching hospital: an observational prospective study - Ambike, Deepali A.; Haribhakta, Sandhya V.; Mundlod, Suryakant; Soni, Seema P.; Sayyad, Rijwana; Bijraniya, Komal (International Journal of Contemporary Pediatrics, 2021)
Background: The likelihood of newborns acquiring severe acute respiratory syndrome coronavirus 2 (SARS- CoV-2) from infected mothers has raised concerns among families and clinicians worldwide. The disease seems to be mild in children and, to date; there are few reports in neonatal population. The aim of the study was to study the Prevalence of Neonatal SARS-CoV-2 infection in a tertiary care teaching hospital. The objective of the study was to study correlation of clinical features and laboratory parameters among SARS-CoV-2 positive neonates. Methods: Prospective observational study conducted in a dedicated COVID-19 tertiary care hospital and Postgraduate Institute in Pune, Maharashtra between May 2020 and August 2020 on a sample size of 55 COVID suspect neonates as they were admitted and diagnosed during the pandemic. Results: Out of 250 COVID positive mothers admitted, 55 COVID suspect neonates were admitted as their mothers were symptomatic. Among 55 suspect neonates, 11 turned out to be positive (20%). Out of 11 COVID positive neonates, tachypnea with requirement of non-invasive O2 in 2 (18%), feeding intolerance in 2 (18%), fever in 2 (18%) rash 1 (9%) was seen. out of the 11 COVID positive neonates admitted, 45% had elevated D-Dimer levels, 36% had elevated Leucocyte counts, 27% each had raised serum ferritin and fibrinogen levels and 18% had raised CRP Levels. Conclusions: We conclude that inspite of the first wave of COVID seen in neonates which was rare then, clinical and laboratory markers showed a good co-relation in our study in all neonates who were COVID positive but there was no radiological co-relation in any. However, all recovered with symptomatic treatment without any specific COVID treatment.